Negotiating existential concerns of death and meaninglessness through the Grotesque in Oscar Wilde’s The Centerville Ghost - Beng, Seach Jin; Ali Termizi, Arbaayah; Talif, Rosli; Zainal, Zainor Izat (UKM Press, 2020)
Grotesque and existentialism in the field of literature generally raise four points. On the one hand, the grotesque has always been associated with negative connotation elements that usually include deformity, death, violence or monstrosity. In fact, the grotesque often carries pejorative connotations for it challenges traditions and deviates from what is accepted as the norm. On the other hand, existentialism, traced way back to as early as the 19th century, often question the meaning of life and struggle with the anxiety of death while constantly looking for ways to justify one’s existence in a world that is filled with pessimism. Thus, this paper aims to find a point of convergence between existentialism and the grotesque by primarily focusing on how the male protagonist, Sir Simon in Oscar Wilde’s The Canterville Ghost employs the grotesque as a way to deal with existential concerns as pointed out by Irvin Yalom namely death, meaninglessness, freedom and existential isolation with an emphasis on the first two concerns. Three grotesque elements, specifically, Bakhtin’s carnivalesque, Thomson’s exaggeration, and Kohut’s narcissism will be studied alongside the two existential concerns, death and meaninglessness. By focusing on grotesque and existential elements, the paper will illustrate how the male protagonist is able to rely on the grotesque to subdue his fear and terror brought upon by the existential concerns in order to justify his sense of existence.